Late Recurrence of Benign Multicystic Peritoneal Mesothelioma Complicated with an Incisional Hernia - Emel Canbay; Haruaki Ishibashi; Shouzou Sako; Toshiyuki Kitai; Eisei Nishino; Yutaka Yonemura (Case Reports in Surgery)
Benign multicystic peritoneal mesothelioma (BMPM) is a rare disease arising from the peritoneal mesothelium. Here, we report a 57-year-old woman admitted to our unit with an incisional hernia fifteen years later following her first operation due to BMPM. Computerized tomography demonstrated a cystic appearing mass with intraabdominal extension in hernia sac. The patient underwent en bloc resection of the mass and hernia repair. An immunohistochemical analysis of the mass confirmed the recurrence of BMPM. Our case supports that BMPM has slowly progressive nature and can recur with complicated incisional hernia long time after primary resection. Diagnosis and long-term followup are crucial for clarifying the characteristics of this disease.